Clinical characteristics, treatment, and blood pressure control in patients with hypertension seen by primary care physicians in Spain: the IBERICAN study - Prieto-Díaz, Miguel A.; Pallares-Carratala, Vicente; Manuel Micó-Pérez, Rafael; Escobar-Cervantes, Carlos; Martín-Sanchez, Vicente; Coca, Antonio; Barquilla-García, Alfonso; Velilla-Zancada, Sonsoles M.; Polo-García, José; Segura-Fragoso, Antonio; Ginel-Mendoza, Leovigildo; Hermida-Ameijerias, Álvaro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives To determine the clinical profile, according to the history of hypertension, the risk of developing hypertension, current antihypertensive treatment and BP control rates in patients with hypertension from the IBERICAN cohort. Methods IBERICAN is an ongoing prospective cohort study, whose primary objective is to determine the frequency, incidence, and distribution of CVRF in the adult Spanish population seen in primary care settings. This analysis shows the baseline clinical characteristics of patients with hypertension. Adequate BP control was defined as BP <140/90 mmHg according to 2013 ESH/ESC guidelines. Results A total of 8,066 patients were consecutively included, of whom 3,860 (48.0%) had hypertension. These patients were older (65.8 ± 10.9 vs. 51.6 ± 14.7 years; p < 0.001), had more cardiovascular risk factors, target organ damage and cardiovascular disease (CVD) in comparison with those without hypertension. The risk of hypertension increased with the presence of associated CV risk factors and comorbidities, particularly diabetes, obesity and the metabolic syndrome, and decreased with the intensity of physical activity. Regarding antihypertensive treatments, 6.1% of patients did not take any medication, 38.8% were taking one antihypertensive drug, 35.5% two drugs, and 19.6% three or more antihypertensive drugs. Overall, 58.3% achieved BP goals <140/90 mmHg. A greater probability of BP control was observed with increasing age of patients and the greater number of antihypertensive drugs. Blood pressure control was lower in hypertensive patients with diabetes, obesity, the metabolic syndrome, increased urinary albumin excretion, higher pulse pressure, and lack of antihypertensive treatment. Conclusions About half of patients attended in primary care settings have hypertension in Spain. Patients with hypertension have a worse CV clinical profile than non-hypertensive patients, with greater association of CVRF and CVD. Around four out of ten patients do not achieve the recommended BP goals, and higher use of combination therapies is associated with a better BP control.